2012
DOI: 10.1002/masy.201250609
|View full text |Cite
|
Sign up to set email alerts
|

Autoadhesion of Glassy Polymers

Abstract: Summary: Thick bulk films of linear amorphous polymers with different chain architecture and molecular weight were brought into contact with themselves in a lap-shear joint geometry at bonding temperatures (T) below the glass transition temperatures of their bulk (T bulk g ), at a small contact pressure, in order to form autoadhesive joints. As-bonded joints were shear-fractured in tension at ambient temperature, and their lap-shear strength was measured as a function of T, bonding time and molecular weight. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Recently, McGraw et al [21] have performed crazing measurements to probe the interdiffusion between two thin films of entangled polymers and showed that it takes less than one bulk reptation time to observe the structural characteristics of bulk crazes at the interface. Similar conclusions about the recovery of interfacial strength have been obtained from lap-joint shear tests [22][23][24][25]. These studies determined the ultimate shear stress at failure and correlated it with interdiffusion time.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…Recently, McGraw et al [21] have performed crazing measurements to probe the interdiffusion between two thin films of entangled polymers and showed that it takes less than one bulk reptation time to observe the structural characteristics of bulk crazes at the interface. Similar conclusions about the recovery of interfacial strength have been obtained from lap-joint shear tests [22][23][24][25]. These studies determined the ultimate shear stress at failure and correlated it with interdiffusion time.…”
supporting
confidence: 68%
“…As in previous simulations [32], we determined the interfacial strength using a shear test that is similar to a lap-joint shear experiment [22][23][24][25]. To focus on a region of width H near the interface, atoms in top (z > H/2) and bottom (z < −H/2) layers were held rigid and displaced at constant velocity in opposite directions in the xy−plane.…”
Section: Interface Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent work, we have used simulations to follow the evolution of the shear strength of interfaces between miscible and immiscible polymers . The maximum shear stress before failure σ max was evaluated using a geometry that mimics a lap-joint shear experiment. As in experiments, we found that σ max rose with welding time t as t 1/4 and saturated long before polymers had diffused by their radius of gyration. In contrast to experiments, simulations allowed direct observations of the evolution of topological constraints (TCs) associated with entanglements.…”
Section: Introductionmentioning
confidence: 86%
“…It is known to depend on entanglement formation through diffusion of the chains across the interface, , which can be described by the well-known reptation model . Accordingly, a strong dependence of adhesive fracture toughness ( G α ) on molecular weight ( M w ) and welding time ( t w ) is observed. ,,, Typically, for the adhesive-fracture toughness to reach the value of the bulk-fracture toughness, welding times on the order of the reptation time are needed, which can be excessively long for ultrahigh molecular weight polymers, as the reptation time scales with the third power of the molecular weight. ,, Welding of semicrystalline polymers that have a glass-transition temperature below room temperature can deviate from the classical reptation approach due to an initial nonequilibrium conformation of the chains. , Furthermore, in such materials, the contribution of entanglement formation due to self-diffusion of the polymer chains to the adhesive-fracture toughness below the melting temperature can be partly obscured by cocrystallization of the macromolecular chains across the interface, but full recovery remains a slow process. ,,, …”
Section: Introductionmentioning
confidence: 99%